Factors Relating to The Performance of Health Officers in Emergency Installations (Study at Bahteramas Hospital, Southeast Sulawesi Province) - Yuni Sucitra, Artha; Sunarsih, Sunarsih; Kamalia, La Ode (Waluya The International Science of Health Journal, 2023)
Introduction: Hospital is part of a social and health organization with the function of providing complete services (comprehensive), disease healing (curative) and disease prevention (preventive) to the community. The performance of health workers is a problem that must be overcome, it is because health services determine the quality of hospital services. The performance of health workers can be influenced by workload, work stress, work environment, work fatigue, and the application of SOP. Methods: This type of research uses a quantitative research design with a cross-sectional study design. The total population is 49 people, with a large sample of 44 people. The sampling technique in this study used the Cluster Random Sampling technique, using the Chi-Square Statistical test. Results: The results showed that there was a relationship between workload and the results of the X2count = 7.079, the X2table value = 3.841, and the Phi value = 0.449, work stress with the X2count value = 8.838, the X2table value = 3.841, and the Phi value = 0.494. Conclusion: The performance of health officers influenced by workload, work stress, work environment, work fatigue, and the application of SOPs. It is recommended that the hospital management can pay more attention to their health workers in order to improve the performance of health workers in the ER Bahteramas Hospital, Southeast Sulawesi Province.